Prevalence and Risk Factors of Work-Related Lower Back Pain among Radiographers in the State of Kuwait - Hesham N. Alrowayeh; Musaed Z. Alnaser; Talal A. Alshatti; Raed S. Saeed (Radiology Research and Practice)
Background. Work-related lower back pain (WrLBP) is a global health issue and a rising concern in the State of Kuwait. The prevalence and the risk factors of WrLBP among radiographers are not well documented. Objective. The purpose of the study was to determine the one-year prevalence, characteristics, impact, and physical risk factors of WrLBP among radiographers in the State of Kuwait. Methods. A self-administered questionnaire was distributed to 200 radiographers. The questionnaire collected data on demographics, physical risk factors, and the occurrence of WrLBP in the previous 12 months. Descriptive statistics, frequency calculations, and chi-square analyses were performed. Results. One hundred forty-six radiographers completed and returned the questionnaires with a response rate of 73% (146/200). The one-year prevalence of WrLBP was 16%. The prevalence of WrLBP was not significantly associated with the participants’ demographics. Although WrLBP was significantly associated with work demands, the overall impact of WrLBP on work duties was minimal. Conclusions. The occurrence of WrLBP among radiographers in Kuwait was low, particularly when compared to healthcare providers involved in more patient handling and direct contact. However, various physical risk factors were identified. Further research is needed to investigate the effect of a treatment and prevention program on the prevalence of WrLBP.